Study of Dimensional Stability of Oil Palm Empty Fruit Bunch Cement Boards Based on Different Temperatures in Hot Water Treatment - Tamliha, Muhammad Alif; Nik Soh, Nik Zaini (Recent Trends in Civil Engineering and Built Environment, 2025)
Malaysia is one of the largest producers of oil palm, this means that tonnes of empty fruit bunch produced which may lead to agricultural waste. Oil Palm Empty fruit bunch (OPEFB) is one of the natural fibres that can be utilized as reinforcement in cement. The replacement also can reduce and minimize the demand for forest resources which is not good for the sustainability of wood. The presence of hydrophilic in the EFB fibre will affect the dimensional stability of the cement board. The higher the presence of hydrophilic in fibre, the lower the dimensional stability of the cement board will occur. The objectives for this study were to determine the effect of EFB fibre using different temperature of hot water treatment method on dimension stability and to analyse the effect of dimensional stability EFB fibre cement board on physical and mechanical performance. Different temperatures for hot water treatment used in this study which were hot water at 80oC and 90oC and 100oC. This treatment were carried out for 3 hours. The density of cement board that will be produced is 1300 kg/m3 and the ratio between cement and fibre that will be used is 3.5:1. 3 samples will be produced for each temperature which makes a total of 9 samples for this study. Based on the physical properties test have conducted, the trend shows that the higher the temperature of treatment imposed on the EFB fibre, the lower the bonding occurred between the fibre and cement. As the bonding between the cement and EFB fibre weak, the lower the physical properties of the EFBCB. The impact of the temperature of treatment with mechanical properties was directly proportional. The higher the treatment of EFB fibre, the lower the strength of the EFBCB. As the study conducted, the dimensional stability of EFBCB will not stable as the temperature rise high.